Islamic Finance and the Convergence towards International Financial Reporting Standards (IFRS): The State of Research Development - Ratna Mulyany; Noraini Mohd. Ariffin (Universitas Syiah Kuala, 2018)
Objective – Extensive research has been undertaken in the area of accounting harmonization ever since the idea of harmonizing accounting standards and practices was probably initiated as early as 1930s. The transformation of International Accounting Standard Committee (IASC) into International Accounting Standard Board (IASB) in 2001, which refines the harmonization agenda into convergence initiative, has escalated the academic research devoted in this field. Nevertheless within the broad research theme of International accounting harmonization and convergence (IAHC), quite limited studies have looked at the issues of IAHC and linking it to the development of Islamic banking and finance. Not until recently where quite significant acknowledgement has been given on this issue especially by the industry community, the earlier development of research in IAHC has not sufficiently covered the interaction between IAHC and the Islamic financial industry. Departing from this context, this paper aims to review the development of research that particularly looked into the issues of IAHC in relation to the Islamic financial industry.Design/methodology – This study was conducted based on rigorous literature review about the topic to identify gaps or inconsistencies in a body of knowledge.Results – Research in IAHC has progressed over the time evidenced with the various topics that have been studied within this theme. Of the broad research theme within IAHC is its interaction with the growing Islamic financial industry. While the reviewed studies in this paper have provided preliminary path in identifying the challenges of IAHC in relation to the financial reporting of Islamic banks (IBs), however there is lacking studies that theoretically and practically examines areas of incompatibility which may prove to be obstacles to the IAHC process and other important elements such as to understand what could be the possible approach to be pursued by IBs within the overall objective of IAHC or IFRS convergence specifically. Most studies within this theme are notably descriptive in nature and few has utilized the empirical method in their analysis.Research limitations/implications – This study is limited in its method of merely reviewing the literature. The use of other various methods may provide more meaningful findings. The result of this study nevertheless implies that further comprehensive research involving standard setters and regulators is viewed as an important future step in resolving the reporting issues for Islamic financial institutions. Given the unresolved dimensions between the adoption of IFRS and the application of Islamic financial activities, the issues examined in this study will continue to be highly relevant, as the Islamic financial industry expands further.Novelty/Originality – A review of researches in IAHC with particular reference to the unique accounting requirements of Islamic financial entities is still limited thus this study perhaps has sketched a map of overall studies that have been performed and shed the light for future areas to be researched within this themeKeywords Islamic Finance, IFRS Convergence, Accounting Harmonization